2006
DOI: 10.1007/s10764-006-9039-y
|View full text |Cite
|
Sign up to set email alerts
|

Postconflict Affiliation Between Former Opponents in Macaca thibetana on Mt. Huangshan, China

Abstract: We describe basic patterns of postconflict affiliation between former opponents within a group of wild, provisioned Tibetan macaques (Macaca thibetana) on Mt. Huangshan, China. Like most primates studied to date, Tibetan macaques reconciled, i.e., overall they engaged in affiliative interaction with opponents at higher rates immediately after an aggressive conflict than at other times. Probabilities of affiliation were enhanced ≤30 s after the end of hostilities. However when we examined sex partner combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
(81 reference statements)
2
21
0
Order By: Relevance
“…It seems likely that having more potential partners allows for, or may even require, the expression of tolerant dominance relationships and strong male bonding. Berman et al (2006) suggested that the nearly even sex ratio, rather than the high degree of sexual dimorphism, may account for the increased male-male tolerance in Tibetan macaques. However, it is difficult to separate the influence of body size and sex ratio in Assamese, Tibetan, and Barbary macaques because all 3 species have large males (Smith and Jungers 1997) and nearly even sex ratios (Fooden 1986;Menard and Vallet 1996;Zhao and Deng 1988).…”
Section: Male Social Relationshipsmentioning
confidence: 99%
“…It seems likely that having more potential partners allows for, or may even require, the expression of tolerant dominance relationships and strong male bonding. Berman et al (2006) suggested that the nearly even sex ratio, rather than the high degree of sexual dimorphism, may account for the increased male-male tolerance in Tibetan macaques. However, it is difficult to separate the influence of body size and sex ratio in Assamese, Tibetan, and Barbary macaques because all 3 species have large males (Smith and Jungers 1997) and nearly even sex ratios (Fooden 1986;Menard and Vallet 1996;Zhao and Deng 1988).…”
Section: Male Social Relationshipsmentioning
confidence: 99%
“…Female Tibetan macaques are reported to form linear dominance hierarchies based on patterns of maternal kinship, and individuals appear to use information on both rank and kinship in social interactions [Bermanet al, 2008;Li, 1999]. Berman et al [2006] report that among female-female dyads, there was "no evidence that tolerant interaction was disrupted after conflicts" suggesting that dominance hierarchies may be relatively stable or that after disputes females are able to reestablish social relationships without the need for reconciliatory behavior. Berman et al [2006] report that among female-female dyads, there was "no evidence that tolerant interaction was disrupted after conflicts" suggesting that dominance hierarchies may be relatively stable or that after disputes females are able to reestablish social relationships without the need for reconciliatory behavior.…”
Section: Introductionmentioning
confidence: 99%
“… *: indicates that there is debate about the classification of the dominance style of this species.1 [12].2 [51].3 [105].4 [107][109].5 [106],[150].6 [80],[118].7 [112].8 [151].9 [18],[152].10 [63].11 [19],[29],[153].12 [154].13 [155].14 [7].15 [27].16 [156].17 [105].18 [157].19 [21],[125].20 [20].21 [158].…”
Section: Introductionmentioning
confidence: 99%